Antiviral roles of eosinophils in asthma and respiratory viral infection - Sasaki, Hisashi; Miyata, Jun; Kawana, Akihiko; Fukunaga, Koichi (Frontiers in Allergy, 2025)
Eosinophils are immune cells that are crucial for the pathogenesis of allergic diseases, such as asthma. These cells play multifunctional roles in various situations, including infection. They are activated during viral infections and exert antiviral activity. Pattern recognition receptors, toll-like receptor 7 and retinoic acid inducible gene-I, are important for the recognition and capture of RNA viruses. In addition, intracellular granule proteins (eosinophil cationic protein and eosinophil-derived neurotoxin) and intracellular nitric oxide production inactivate and/or degrade RNA viruses. Interestingly, eosinophil-synthesizing specialized pro-resolving mediators possess antiviral properties that inhibit viral replication. Thus, eosinophils may play a protective role during respiratory virus infections. Notably, antiviral activities are impaired in patients with asthma, and eosinophil activities are perturbed in proportion with the severity of asthma. The exact roles of eosinophils in RNA virus (rhinovirus, respiratory syncytial virus, and influenza virus)-induced type 2 inflammation-based asthma exacerbation remain unclear. Our research demonstrates that interferons (IFN-α and IFN-γ) stimulate human eosinophils to upregulate antiviral molecules, including guanylate-binding proteins and tripartite motifs. Furthermore, IFN-γ specifically increases the expression of IL5RA, ICAM-1, and FCGR1A, potentially enhancing cellular responsiveness to IL-5, ICAM-1-mediated adhesion to rhinoviruses, and IgG-induced inflammatory responses, respectively. In this review, we have summarized the relationship between viral infections and asthma and the mechanisms underlying the development of antiviral functions of human and mouse eosinophils in vivo and in vitro.